TROMBOSITOPENIA DAN HEMORAGIK PADA ANAK DENGAN DEMAM BERDARAH DENGUE (DBD): KAJIAN LITERATUR - Miftahuz Zakiyah; Ilham Fathurrahman; Nadya Syarifatul Fajriyah; Suharno Zen; Yuda Nabella Prameswari; Benedikta Diah Saraswati (Prodi Sains Biomedis Fakultas Ilmu Kesehatan Universitas Muhammadiyah Metro, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major cause of morbidity among children in Indonesia. Thrombocytopenia is one of the key hematological abnormalities associated with progression to hemorrhagic manifestations.This review aims to summarize current evidence related to thrombocytopenia and clinical hemorrhagic features in pediatric DHF based on several Indonesian studies. A narrative review was conducted using 20 references focusing on pediatric DHF, thrombocytopenia, clinical manifestations, and disease severity.Data from the reviewed studies indicate that thrombocytopenia occurs in more than 70% of DHF cases and typically worsens around days 3–7 of fever. Hemorrhagic manifestations such as petechiae, gum bleeding, and prolonged fever duration are associated with lower platelet count and higher disease severity. Nutritional status, duration of fever, and clinical progression also influence the degree of hemorrhage in children. Thrombocytopenia is a consistent predictor of hemorrhagic complications in pediatric DHF. Early recognition of platelet decline and clinical bleeding signs is crucial in preventing progression to severe dengue.